2015
DOI: 10.1371/journal.pone.0125783
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Adapter Molecule MTSS1 as a Potential Oncogene-Specific Tumor Suppressor in Acute Myeloid Leukemia

Abstract: The adapter protein metastasis suppressor 1 (MTSS1) is implicated as a tumor suppressor or tumor promoter, depending on the type of solid cancer. Here, we identified Mtss1 expression to be increased in AML subsets with favorable outcome, while suppressed in high risk AML patients. High expression of MTSS1 predicted better clinical outcome of patients with normal-karyotype AML. Mechanistically, MTSS1 expression was negatively regulated by FLT3-ITD signaling but enhanced by the AML1-ETO fusion protein. DNMT3B, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 34 publications
(51 reference statements)
1
15
0
Order By: Relevance
“…Consistent with this role, expression of MTSS1 is decreased in breast, esophageal, bladder, kidney, gastric, pancreatic, ovarian and CRC, 30–33,4247 as well as in acute and chronic myeloid leukemia, where it has been shown to function as a tumor suppressor. 48,49 Our analysis of TCGA data sets also demonstrated reduced expression of MTSS1 in human CRC tissue samples. However, a contradictory report indicating that MTSS1 over-expression increases the metastatic capacity of melanoma cells 50 points to potential functional complexity of this protein.…”
Section: Discussionmentioning
confidence: 62%
“…Consistent with this role, expression of MTSS1 is decreased in breast, esophageal, bladder, kidney, gastric, pancreatic, ovarian and CRC, 30–33,4247 as well as in acute and chronic myeloid leukemia, where it has been shown to function as a tumor suppressor. 48,49 Our analysis of TCGA data sets also demonstrated reduced expression of MTSS1 in human CRC tissue samples. However, a contradictory report indicating that MTSS1 over-expression increases the metastatic capacity of melanoma cells 50 points to potential functional complexity of this protein.…”
Section: Discussionmentioning
confidence: 62%
“…Interestingly, the candidacy of MTSS1 as a potent tumor suppressor has also been demonstrated in normal karyotype AML patients. [23] More recently, a novel murine model capable of simulating progression of human CML, in particular transformation to myeloid blast crisis, has been engineered. [24] This should enable a better understanding of the molecular pathogenesis of blast crisis and inform on candidate therapeutic targets.…”
Section: Updates On Genetics and Biology From Mouse Mpn Modelsmentioning
confidence: 99%
“…MTSS1 expression levels were increased in tissues adjacent to carcinoma, but clearly reduced in cancer tissues, and MTSS1 expression levels were gradually reduced as histological differentiation degree decreased (12). In the hematopoietic system, MTSS1-knockout mice had an increased propensity to develop aggressive B cell lymphomas (13,14). These studies suggested that MTSS1 acts as a tumor metastasis suppressor gene in these malignancies, that low MTSS1 expression levels confer a poorer prognosis and that higher expression levels correlate with improved overall survival rates.…”
Section: Effect Of Metastasis Suppressor 1 On H1299 Cells and Its CLImentioning
confidence: 99%